CARS microscopy as a tool for studying the distribution of micronised drugs in adhesive mixtures for inhalation1. (1st June 2014) - Fussell, Andrew L.; Grasmeijer, Floris; Frijlink, Henderik W.; de Boer, Anne H.; Offerhaus, Herman L.; Moger, Julian; Radi, Peter
<x xml:space="preserve">Abstract</x> Drug particles can be produced in the proper aerodynamic particle size distribution (PSD) for inhalation by techniques such as micronisation or spray drying (1–5 µm). However, mixing with coarse carrier particles may change the PSD by agglomeration. Furthermore, the spatial distribution of the drug particles on the carrier particles in adhesive mixtures is highly relevant to the dispersion performance of inhalation powders. Coherent anti‐Stokes Raman scattering (CARS) microscopy is capable of chemically selective imaging, allowing the distribution of drug particles on the surface of carrier particles to be visualised. We used CARS microscopy to image the drug distribution for budesonide and salmeterol on the surface of lactose carrier particles. Image analysis was performed to determine the drug PSD that was then compared with the PSD obtained from laser diffraction. Additionally, comparative CARS and scanning electron microscopy (SEM) images were recorded to allow a direct comparison of the images obtained from CARS microscopy and from SEM. CARS microscopy revealed the drug to be in clusters on the surface of the carrier particles, while the image analysis identified 68% of the particles to have a median area of 0.4 µm2. Image analysis resulted in measurement of larger particles than laser diffraction, which may be caused by agglomeration during mixing. The combined chemical and morphological information from comparative CARS and SEM analysis resulted in unambiguous identification of the spatial drug distribution over the carrier surface. Our results indicate that CARS microscopy is a useful tool to study adhesive mixtures for inhalation. Copyright © 2014 John Wiley & Sons, Ltd.